Luminescence of PbI₂ nanoinclusions in CdI₂ crystal lattice - Bolesta, I.M.; Vistovskyy, V.V.; Gloskovska, N.V.; Rovetskij, I.M. (Functional Materials, 2016)
Luminescence spectra of CdI₂ crystals with PbI₂ inclusions (10⁻⁵%) under synchrotron excitation at 8 K are examined in the present work. The spectra of the crystals grown from the melt exhibit luminescence peaks at 2.13 and 2.43 eV which are associated with one-dimensional impurity nanoinclusions near dislocations. In the luminescence spectra of CdI₂ crystals synthesized by the method of diffusion from the gas phase the effect of two-dimensional PbI₂ nanoinclusions with 2.0 and 2.48 eV bands prevails. A new model of the luminescence center is proposed.